FUNGSI SUBJEK DALAM PIDATO SAN BERNARDINO TERROR ATTACK AND THE WAR ON ISIS OLEH BARACK OBAMA ( SEBUAH ANALISIS SINTAKSIS) - WAGUNU, OSINNIAWATI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research is entitled ? The Function of Subject Used in the Speech San Bernardino Terror Attack and the War on ISIS by Barack Obama?. The objectives of this research are to identify and classify the types of functions subject and to analyze the realizations of functions subject. This research uses a descriptive method. There are three steps to finish this research. First step is preparation, the writer reads the speech to find out the data. Second step is data collection. The writer collects the subject found in the speech and compares them with the speech text then the writer identifies and classifies the kinds of function subject according to the theory of Aarts and Aarts (1982). Third step is data analysis, to analyze the data about the realizations of functions subject, the writer uses the theory from Aarts and Aarts (1982) to analyze and describe the realizations of function subejct. The result of this research: First, it shows that according to the theory of Aarts and Aarts (1982), there are four criteria of functions subject, but there were only three criteria of function subject found in this speech, those are Position, Concord, Passivization. Furthermore, the six realizations of function subject, those are Noun Phrase, Finite Clause, Non- Finite Clause, Anticipatory it + Finite/Non-Finite Clause, Unstressed there in existential sentences, and Prepositional Phrase found in the speech San Bernardino Terror Attack and the War On ISIS. The findings of this research support the theory of Aarts and Aarts (1982). Keywords: Function Subject; Obama?s Speech, Syntax; Aarts and Aarts